The Relationship between Waist Circumference and Low-Density Lipoprotein (LDL) Levels among Postmenopausal Women in the Working Area of Puskesmas Negeri Laha-Tawiri - Ariwita Deli; Mutmainnah Abbas; Ritha Tahitu; Rosdiana Mus; Indrawati Kusadhiani; Dylan Tamalsir (Faculty of Medicine, Universitas Tadulako, 2026)
Background: Cardiovascular disease remains a major cause of morbidity and mortality among postmenopausal women, with central obesity and dyslipidemia identified as key risk factors. Waist circumference is a simple anthropometric measure that may reflect lipid profile changes, particularly in low-density lipoprotein (LDL) levels. Objectives: This study aimed to determine the relationship between waist circumference and LDL levels in postmenopausal women in the working area of Puskesmas Negeri Laha-Tawiri, Ambon. Methods: A cross-sectional study was conducted involving 60 postmenopausal women selected through purposive sampling. Waist circumference was measured using a standardized tape, and LDL levels were assessed through laboratory blood tests. Data were analyzed using descriptive statistics and Pearson correlation test with a significance level of p < 0.05. Results: The analysis revealed a significant positive correlation between waist circumference and LDL levels (r = 0.42, p = 0.003), indicating that greater abdominal obesity was associated with higher LDL levels. Conclusions: Waist circumference is strongly related to LDL levels among postmenopausal women, suggesting that it can serve as a simple and non-invasive screening tool for early detection of dyslipidemia. Preventive strategies focusing on lifestyle modification are recommended to reduce cardiovascular risk in this population.